2008
DOI: 10.1097/mlg.0b013e31815d8e68
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Electroneurography and Electromyography in Facial Palsy

Abstract: Objectives:To compare the prognostic value of electroneurography (ENG) and needle electromyography (EMG) to estimate facial function outcome after acute facial palsy.Study Design: Retrospective study using electrodiagnostic data and medical chart review.Methods: Two hundred one patients treated 1995 to 2004 were included. Initial and final facial function was established clinically by the House-Brackmann (HB) scale. ENG results were classified into amplitude loss less than 75% and amplitude loss 75% or greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 11 publications
5
77
1
5
Order By: Relevance
“…Using previously described methods, we found that the accuracies of ENoG and EMG, 76.4 and 84.7%, respectively, were similar to those of previous reports, in which these two methods showed accuracies of 73 and 89%, respectively [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using previously described methods, we found that the accuracies of ENoG and EMG, 76.4 and 84.7%, respectively, were similar to those of previous reports, in which these two methods showed accuracies of 73 and 89%, respectively [11].…”
Section: Discussionsupporting
confidence: 89%
“…A ground electrode was attached to the arm of each patient and a recording electrode was placed in the nasolabial fold. Measurements were reported as the percent maximal amplitude on the side of the lesion/maximal amplitude of on the healthy side of the compound myoaction potential (CMAP) obtained from the nasalis muscle measured at the suprathreshold stimulation [11]. Incomplete recovery was defined as a [90% loss of amplitude on ENoG.…”
Section: Methodsmentioning
confidence: 99%
“…Wie von den Freiburger Autoren richtig aufgezeigt, unterscheidet sich die Prognose bei Schwangeren nicht von der Prognose bei anderen Patienten. Richtungweisend ist hier wie bei allen anderen Patienten auch die Elektrodiagnostik [3,4]. Von Interesse wäre es zu untersuchen, ob bei Schwangeren mit Fazialisparese und dem Risikofaktor Hypertonus oder Adipositas gehäuft degenerative Paresen nachzuweisen sind.…”
Section: Ist Die Fazialisparese In Der Schwangerschaft Ein Eigenes Krunclassified
“…Out of this 19 patients had idiopathic facial nerve paralysis (Bell's palsy) and seven had late onset post traumatic facial nerve palsy. Electroneuronography was carried out and patients with House-Brackmann grade II and grade III injury were included in the study [8].…”
Section: Methodsmentioning
confidence: 99%